Spatio-Temporal Habitat Dynamics of Migratory Small Yellow Croaker (Larimichthys polyactis) in Hangzhou Bay, China - Xiangyu Long; Dong Wang; Pengbo Song; Mengwen Han; Rijin Jiang; Yongdong Zhou (Fishes, 2025)
The small yellow croaker (Larimichthys polyactis), a migratory estuarine-demersal fish critical to East Asian fisheries, has faced severe population declines because of anthropogenic pressures (e.g., overfishing and anthropogenic habitat modification) and shifting environmental conditions. This study investigates its spatio-temporal habitat dynamics in Hangzhou Bay (2017–2023) using fisheries surveys and species distribution models (SDMs), with insights applicable to Pacific Coast migratory fish conservation. We evaluated the performance of eleven modeling algorithms to identify the most accurate model for predicting small yellow croaker distributions. Our results showed that the random forest algorithm outperformed other models, with a high sensitivity (95.238) and specificity (99.49), demonstrating its ability to capture complex non-linear relationships between environmental factors and species distribution. Depth emerged as the most influential factor, accounting for 30% of the importance in the model, with small yellow croakers preferring deeper waters around 60 m. Salinity was the second most important factor, with higher occurrence probabilities in areas where salinity exceeded 25 PSU. Other environmental factors, such as temperature and dissolved oxygen, had relatively smaller impacts on distribution. Spatially, small yellow croakers were predominantly distributed in offshore regions east of 122.5° E, where deeper waters and higher salinity levels provided suitable habitat conditions. This study underscores the need for targeted management measures, such as habitat restoration, to ensure the sustainable management of small-bodied yellow croaker populations.